Evaluation of Water Suitability for Sustainable Seaweed (Kappaphycus Alvarezii) Cultivation to Support Science Technopark in North Kalimantan - Maradhy, Ermawaty; Nazriel, Rizal Syarief; Sutjahjo, Surjono Hadi; Rusli, Meika Syahbana; Widiatmaka, Widiatmaka; Sondita, M. Fedi Alfiadi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Tarakan dry seaweed production increased during 2012-2018 for the cultivation of Kappaphycus alvarezii with the longline planting method. This study aims to assess the quality of the waters and their suitability for seaweed cultivation on the coast of Tarakan Island. The environmental parameters of water quality measured were chlorophyll-a, water temperature, salinity, pH, DO, TDS, turbidity, nitrate, phosphate, water depth, current velocity, protection, research location, and distance between settlements. The study was conducted with in-situ and ex-situ measurements based on APHA (2012). Water samples were taken using the multi-parameter Horiba U51. chlorophyll-a was analyzed using spectrophotometric methods, nitrate levels were analyzed using SNI 06-6989.79-2011, while phosphates were analyzed using SNI 06-6989.31-2005.The suitability of the waters is divided into 4 classes, S1 (very suitable), S2 (suitable), S3 (marginally suitable), and N (not suitable). The results showed that the coast of Tarakan Island has 3 categories, namely marginally suitable (S3) 13.20%, suitable (S2) 86.50%, and very suitable (S1) 0.30%. The existing condition of the coastal waters of Tarakan Island supports the cultivation of K. alvarezii seaweed. Tarakan Island coastal existing condition as an areal support seaweed cultivation K. alvarezii with the potential to be developed land area of 33896.73 ha.